Analysis of Concept Understanding Test Items on Static Fluid Material Using Rasch Model - Irawan, Ivan Danar Aditya; Indraloka, Ristanti Mulia; Basri, Nur Akhyar; Salmah, Ummi; Parno, Parno (Universitas Muhammadiyah Makassar, 2025)
Conceptual understanding is a vital component in physics education, particularly for static fluid concepts, which are often sources of misconceptions among students. Common misunderstandings include incorrect interpretations of hydrostatic pressure and Pascal's law. This study aims to develop and analyze a conceptual understanding test instrument for static fluid materials using the Rasch Model. A descriptive quantitative research design was employed, involving 75 eleventh-grade students from three high schools in Lumajang and Malang, selected through cluster random sampling. The instrument comprised 16 multiple-choice questions based on eight conceptual indicators and underwent expert validation by two physics teachers. Data were analyzed using the Winstep application to assess validity, reliability, difficulty level, and item discrimination. The results revealed that 12 out of 16 test items met the validity criteria, with an expert validation score of 98.3% categorized as